Intra-Articular Corticosteroid Injection + Oral Antibiotics and Joint Drainage as Outpatient Treatment for Knee Septic Arthritis - Andersen; Ganda Purba (PT Kalbe Farma Tbk., 2020)
Septic arthritis caused by bacterial infection is a serious disease and the prognosis has not improved significantly over the past two decades. The most often etiology is Staphylococcus aureus. The diagnosis of septic arthritis rests on isolation of the pathogen from joint fluid. Appropriate antibiotic treatment and adequate joint drainage should begin immediately in suspected septic arthritis after collection of proper sample for microbiologic studies. This case was treated with intra-articular triamcinolon acetonide injection, oral amoxicilin-clavulanate, and needle aspiration for joint drainage. Artritis septik yang disebabkan infeksi bakteri merupakan penyakit serius dan prognosisnya tidak membaik dalam beberapa tahun. Etiologi tersering artritis septik adalah Staphyloccocus aureus. Diagnosis artritis septik harus berdasarkan isolasi bakteri patogen dari cairan sendi. Pemberian antibiotik dan drainase cairan sendi harus segera jika dicurigai artritis septik setelah sediaan mikrobiologi diambil. Kasus ini menggunakan injeksi kortikosteroid triamcinolon acetonide ke dalam sendi lutut bersamaan dengan antibiotik oral amoksilin-klavulanat dan aspirasi cairan sendi untuk drainase.